2021
DOI: 10.30743/best.v4i2.4322
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Kesulitan Belajar Siswa Pada Materi Monera

Abstract: Penelitian ini bertujuan untuk mengetahui presentase ketuntasan belajar, analisis kesulitan belajar serta penyebab kesulitan belajar siswa dalam mempelajari materi monera. Jenis penelitian yang digunakan yaitu deskriptif kunatitatif. Populasi penelitian adalah seluruh siswa kelas X IPA yang terdiri 142 siswa. Sampel penelitian berjumlah 45 siswa dan diambil menggunkan teknik simple random sampling. Analisis data menggunakan statistik deskriptif. Teknik pengumpulan data menggunakan tes, angket, dan wawancara. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…Encouraging motivation in learning is one of the things that needs to be raised in learning efforts at school (Dewi et al, 2019). The learning motivation that students have in every learning activity plays a very important role in improving student learning achievement in certain subjects (Ayu Lestari et al, 2023). This learning motivation aims to ensure that students who become students do not feel bored when receiving the material taught by the teacher.…”
Section: Introductionmentioning
confidence: 99%
“…Encouraging motivation in learning is one of the things that needs to be raised in learning efforts at school (Dewi et al, 2019). The learning motivation that students have in every learning activity plays a very important role in improving student learning achievement in certain subjects (Ayu Lestari et al, 2023). This learning motivation aims to ensure that students who become students do not feel bored when receiving the material taught by the teacher.…”
Section: Introductionmentioning
confidence: 99%
“…The use of this material is due to the role of bacteria in life, providing real issues or impacts on health or the environment, which means that bacteria are always around and students need to be aware of their existence. Maisari & Pranoto (2021) revealed that the factors that caused students' difficulties in learning Monera included students who were not interested in learning Monera due to inadequate learning media and teachers who were unable to connect the material being taught with everyday life. This is the reason that the use of SSI topics that contain real-life issues is an appropriate alternative for teaching the Monera concept to make it more contextual, applicable, and interesting.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1. Data analysis using PRISMA (Preferred Reporting Items for Systematic Reviews and Meta Analysis) diagram,(Zulkarnain et al 2022) …”
mentioning
confidence: 99%